Incentives to Participate in Clinical Trials: Practical and Ethical Considerations - Bernstein, Steven L. (Am J Emerg Med, 2015)
BACKGROUND: Clinical trials often offer incentives to encourage individuals to enroll, and to enhance follow-up. The scope and nature of incentives used in ED-based trials is unknown. OBJECTIVES: To characterize the quantity and quality of incentives and other forms of compensation used in clinical trials of human subjects recruited in U.S. EDs. A secondary goal is to provide an historical and ethical analysis of the use of incentives in clinical trials. METHODS: We reviewed English-language randomized clinical trials conducted in U.S. emergency departments from 2009-2013. Full text of the studies was reviewed to identify whether incentives were used, their value, and timing. Funding source was noted as well. Data are presented with descriptive statistics. RESULTS: Of 1151 papers identified, 76 (6.6%) fit criteria for review. Of these, 7 (9.2%) provided incentive payments. A recently published eighth trial was included as well. The total cash value of incentives offered ranged from $10-195. Four studies offered payment at enrollment only. Incentives included cash, debit cards, and gift cards. CONCLUSION: The use of financial incentives in ED-based trials is uncommon. Studies that employ incentives are generally extramurally funded, usually by a federal agency, and include waves of follow-up that continue after discharge from the ED. Payment size is modest. Incentives may improve recruitment and retention in ED-based trials, but authoritative data are lacking. Investigators need to take care to avoid incentives that may be coercive or unduly influence research participants.